Analisis Kecerdasan Spasial Siswa dalam Menyelesaikan Soal-Soal Geometri Berdasarkan Tingkat Berpikir Van Hiele - Azwar Anwar; Bertu Rianto Takaendengan; Luluk Nirwana; James James (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to describe, identify and analyze students' spatial intelligence in working on geometry problems according to Van Hiele's theory. The method used in this research is descriptive research with a qualitative approach. This research was conducted at SMP Negeri 2 Tarakan. The research instrument used was the Van Hiele geometric thinking level test and spatial ability test, interview guides and documentation. Prior to use, the test, an interview guide, was first validated. The data analysis technique will be used in 4 stages, namely collecting, reducing, presenting, and concluding all the data obtained. The results of this study are that students with high spatial intelligence (KST) are at the level of informal deductive thinking (level 3) where at this ability students are able to know the relationship between shapes. While students with moderate spatial intelligence (SCC) are at the level of analytical thinking (level 2), namely the ability to know and mention the properties of flat shapes. Students with low spatial intelligence (KSR) are at the level of visualization thinking (level 1). In conclusion, it is important for teachers to know students' abilities in learning geometry by paying attention to the level of geometric thinking, being able to use the Van Hiele Geometry learning model, increasing spatial intelligence and van Hiele levels can be done through training involving geometric media or software (geogebra). Keywords: spatial intelligence, geometry, level of thinking, Van Hiele